Ali lahko z dostavnimi sistemi izboljšamo učinkovitost vitaminov in mineralov? - Zupančič, Špela (Farmacevtski vestnik, 2020)
Vitamins and minerals are essential for the functioning of human body and the prevention of diseases. It is desirable to consume an adequate amount with balanced and varied food. However, when this is not possible, they are available as medicinal products, nutritional supplements and cosmetics. Conventional dosage forms, such as tablets, capsules, effervescent tablets and powders for oral use are currently still predominant on the market. Due to the challenging stability, low solubility and bioavailability there is a need to improve the efficacy of vitamins and minerals. One possible way is development of novel advanced delivery systems, the most important among which are liposomes, micro- and nanoemulsions, self(micro)emulsifying systems, solid lipid nanoparticles and nanostructured lipid nanocarriers.
Keywords: Dostavni sistem; Kozmetični izdelki; lipidni dostavni sistemi; Minerali; nanodostavni sistemi; Prehranska dopolnila; Vitamini; Zdravila